CpG Oligodeoxynucleotides Inhibit RANKL-Induced Osteoclast Formation by Upregulating A20 Deubiquitinase in RAW 264.7 Cells. (31st August 2022) - Kim, Seong-Kyu; Choe, Jung-Yoon; Park, Ki-Yeun
Abstract : Objective . Activation of toll-like receptor 9 (TLR9) has been proposed to play an inhibitory role in RANKL-induced osteoclastogenesis. A20 deubiquitinase has been found to be related to bone loss. This study investigated the role of CpG oligodeoxynucleotides (CpG-ODNs) through regulation of A20 deubiquitinase in RANKL-induced osteoclast formation. Methods . RAW 264.7 cells, a murine monocyte-macrophage cell line, were incubated with or without CpG-ODN in the presence of RANKL. Osteoclast-specific genes and their related signaling molecules were measured by real-time quantitative polymerase chain reaction and Western blot assay. Morphological assessment for osteoclast formation was performed using tartrate-resistant acid phosphatase (TRAP) staining and F-actin ring formation staining. Results . RANKL-induced osteoclast-related genes and proteins, c-Fos, NFATc1, TRAP, cathepsin K, and carbonic anhydrase II were significantly inhibited in RAW 264.7 cells stimulated with CpG-ODN. CpG-ODN attenuated TNF receptor-associated factor 6 (TRAF6), p-I κ B α, and p-NF- κ B expression in RAW 264 cells mediated by RANKL. CpG-ODN increased A20 gene and proteins in time-dependent manner. A20 expression under costimulation with CpG-ODN and RANKL was more decreased than under stimulation with RANKL alone. Cells transfected with A20 siRNA augmented expression of osteoclast-related genes and proteins. Number of TRAP-positive cells transfected with A20 siRNA was higher than those transfected with NC siRNA. A20 expression in cells transfected with IL-1 β siRNA in the presence of both RANKL and CpG-ODN was more decreased than those with NC siRNA. Conclusion . This study showed that CpG-ODN suppressed RANKL-induced osteoclast formation through regulation of the A20-TRAF6 axis in RAW 264.7 cells.